Towards a globally collaborative behavioral science: an organizational approach from pandemic psychology - Leander, N Pontus; Lemay Jr., Edward P; Jeronimus, Bertus F.; Keller, Anita C.; PsyCorona Collaborations; Abdul Khaiyom, Jamilah Hanum; et al., (International Society For The Study of Behavioural Development (ISSBD), 2020)
The PsyCorona collaboration is a research project to examine processes involved in the COVID-19 pandemic, such as behavior that curbs virus transmission, which may implicate social norms, cooperation, and self-regulation. The study also examines psychosocial consequences of physical distancing strategies and societal lockdown, such as frustration of psychological and social needs, economic stressors, relationship strains, prejudice, psychological stress, and deteriorating mental health (e.g., Brooks et al., 2020). Related consequences were observed in past epi- demics such as the 1918 flu pandemic (Dolan, 2020; Hon- igsbaum, 2019; Jeronimus, 2020). A global collaboration allows us to study the role of culture, and to make general- izable predictions on societal responses to virus infections. Culture may influence our living arrangements and how easily we adjust and cooperate at the societal level to miti- gate virus transmission. Moreover, because the evolving coronavirus pandemic has implications for ongoing psy- chological and social development, we continue to track people over time.